Story-based mathematics learning: Inspiration from stories in the Qur’an - Chusnia, Rifatul; Fathani, Abdul Halim (SAINTIS Publishing, 2023)
Science is the most essential component that human beings must have because they can distinguish between right and wrong only with science. Allah Almighty gives gifts to humans in the form of reason that can be used to think and develop the science that Allah has created. In Allah’s verse, Surah Al-Mujadalah, verse 11, it is stated that Allah will elevate the degree of a knowledgeable man. Therefore, Muslims are obliged by law to seek knowledge by using the Qur’an and Sunnah as guidelines. Understanding the content of the Qur’an was also necessary; thus, scholars revealed the content of the Qur’an through the stories in the Qur’an. This article discussed the stories in the Qur’an and their integration into mathematics education through story-based methods. The research reason, i.e., many children and the public perception that learning mathematics was not necessary and assumed that mathematics was difficult to understand. This article proposed solutions to overcome these problems through the story method because the stories’ knowledge conveyed would be easier to understand and stuck in the minds of children and society where the story was taken from the stories in the Qur’an.